Zakat as Tax on the Perspective of Islamic Law - Bahri, Andi (State Institute of Islamic Studies (IAIN) Palu, 2017)
Zakat as one of the pillars in Islam with dimensions ubudiyyah, ijtimaiyyah and iqtishadiyyah. As a country with the largest Muslim population in the world, Indonesia will potential benefit in zakat management. Based on calculation, the number of Muslim population will produce more zakat to increase ummah well-being in the zakat is managed in professional and accountable ways. Majority of zakat management problems includes limited qualified human skills and human resources (HR) in zakat management. In addition, weak regulations has also resulted in slow improvment in the optimization of zakat management. As a solution to the chronic problem is to provide urgent solutions in the zakat management organization (OPZ). This includes the involvement of stakeholders (government) in regulating the mechanism of zakat management and promoting public education about the obligations of zakat contribution. The position of zakat profession in Islam has similar position with other zakat income. As the result, the most accurate term given to zakat profession is zakat income (kasab). While the position between zakat and tax, there are three arguments: First, zakat and taxes are equally paid by every taxpayer and zakat obligators. Second, a Muslim chooses either of the two instruments: paying zakat or paying taxes only. Third, a muslim chooses one between; zakat or taxes, and assume his/her choices are representative of both. If he/she pays taxes, then he/she considers the tax as zakat from his property.